2022
DOI: 10.3389/fpubh.2022.1043774
|View full text |Cite
|
Sign up to set email alerts
|

Childcare for farm families: A key strategy to keep children safe yet largely absent from farm programming

Abstract: Despite long-standing safety recommendations that non-working children be supervised off the worksite by an adult, little is known about farm families' ability to comply. We conducted a review of 92 documents and 36 key informant interviews in three U.S. states (Ohio, Vermont, and Wisconsin) to assess how farm service providers and farm organizations address the intersection of children and childcare with farm work and farm safety in programming. Through their programming, these two groups deeply influence far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…System interventions to decrease the demands of farming could help address the stress of women on the farm. Many of our participants reported juggling caring for children, employment, and farming as a part of their stress, and the lack of child care in rural areas is well-documented (F. Becot et al, 2022; Henning-Smith & Kozhimannil, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…System interventions to decrease the demands of farming could help address the stress of women on the farm. Many of our participants reported juggling caring for children, employment, and farming as a part of their stress, and the lack of child care in rural areas is well-documented (F. Becot et al, 2022; Henning-Smith & Kozhimannil, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…More recent research has examined the invisible labor and stress of women on the farm who bear a disproportionate burden in finding and managing child care. F. Becot et al (2022) found that few programs for young farmers or women in farming consider child care needs, with a clear message that child care work is not seen as real farm work. Traditional gendered roles for child care continue on the farm, along with expanded responsibilities for women, creating increasing stress and familial tension (Rissing et al, 2021).…”
Section: Stress and Mental Health In Women In Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed that parents often refer to “common sense” even when they are not modeling safe behaviors themselves ( 21 ). In contrast, some parents would prefer to keep children away from agricultural work areas, but have few alternatives because of the need to keep the farm operational amidst a lack of affordable and accessible childcare ( 22 , 23 ). Adding to this is the challenge of reaching unique populations that harbor traditional practices and religious views regarding youth on farms, such as Plain communities ( 24 ).…”
Section: Impacts and Challengesmentioning
confidence: 99%
“…So, who and what influences farm parents’ safety practices? The economics of agriculture is a primary driver of decisions and many organizations and corporations influence those economics ( 14 , 15 ). While the relative strength of influence is not known, it is believed that production systems, insurers and bankers are influential ( 16 ).…”
Section: Introductionmentioning
confidence: 99%